Curative effect of anti-fibrosis Chinese patent medicines combined with ursodeoxycholic acid for primary biliary cholangitis: A systematic review and meta-analysis - Bi, Yufei; Shi, Ke; Chen, Jialiang; Wang, Xianbo (Frontiers in Pharmacology, 2023)
Objective: To delineate the curative effect and safety of anti-fibrosis Chinese patent medicines (CPMs) combined with ursodeoxycholic acid (UDCA) for primary biliary cholangitis (PBC). Methods: A literature search was conducted using PubMed, Web of Science, Embase, Cochrane Library, Wanfang database, VIP database, China Biology Medicine Database, and Chinese National Knowledge Infrastructure from their inception until August 2022. Randomized controlled trials (RCTs) of the treatment of PBC with anti-fibrotic CPMs were collected. The eligibility of the publications was assessed using the Cochrane risk-of-bias tool. The evaluation indicators were the clinical efficacy rate, liver fibrosis, liver function, immune function, and symptom score. Meta-analysis and subgroup analysis were conducted to evaluate the effectiveness of anti-fibrosis CPMs. Risk ratio (RR) was used to assess dichotomous variables, and continuous variables with a 95% confidence interval were calculated using mean difference. Results: Twenty-two RCTs including 1,725 patients were selected. The findings demonstrated that anti-fibrotic CPMs combined with UDCA improved the efficacy rate, liver function, liver fibrosis, immunological indicators, and clinical symptoms compared with UDCA alone (all p < 0.05). Conclusion: This study demonstrates that the combination of anti-fibrotic CPMs and UDCA can improve both clinical symptoms and outcomes. Nevertheless, more high-quality RCTs are needed to assess the effectiveness of anti-fibrosis CPMs for PBC.